Leadership Role of Madrasah Aliyah Head in Improving The Quality of Education - Salim Salim; Azwardi Azwardi; Mutiara Ritonga; Rica Widiastuty (Tarbawi, 2021)
This study aims to describe the role of principal leadership in improving the quality of Islamic religious education based on the personality of the principal, understanding the vision and mission, and the goals of Islamic religious education. This study uses a qualitative method with a case study approach that focuses on the leadership of the principal in MAS Insan Kesuma Madani. The result is that the leadership competence of the principal is very closely related to the activities of improving the quality of PAI. And the steps taken by the principal in improving the quality of Islamic Education are by increasing the professionalism of PAI teachers. In Madrasah Aliyah Private (MAS), Insan Kesuma Madani has a principal who is able to improve the professionalism of PAI teachers because they have good leadership competencies such as a personality based on the competence of Islamic values, the ability to make decisions that satisfy all parties, an understanding of the vision and mission and learning objectives Islamic education. And steps taken in order to improve teacher professionalism are such as induction of novice teachers; participate in activities such as PPG, workshops, training, and seminars to improve pedagogical competence; Organizing teacher group work activities (KKG) aims to make MAS Insan Kesuma Madani produce graduates who are competitive globally and still have Islamic values.